Patient‐based outcomes of in‐office KTP ablation of vocal fold polyps. (13th November 2013) - Sridharan, Shaum; Achlatis, Stratos; Ruiz, Ryan; Jeswani, Seema; Fang, Yixin; Branski, Ryan C.; Amin, Milan R.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Recent data have suggested that in‐office potassium titanyl phosphate (KTP) laser treatment for benign vocal fold lesions yields significant reduction in lesion size with favorable effects on both mucosal wave and glottic closure. However, these previous studies omitted voice‐related outcomes. We sought to compliment these previous data with voice‐related outcomes in a cohort of patients undergoing KTP ablation of vocal fold polyps. Study Design Retrospective outcomes study. Methods Voice Handicap Index (VHI)−10 and acoustic measures were reviewed for 31 consecutive patients with benign vocal fold polyps treated with in‐office KTP laser surgery. All data were analyzed statistically via a mixed model fit to analyze the data from each of three clinical visits. Results Across all patients, the mean VHI‐10 scores decreased at first follow‐up from 19.7 to 9.7 (P < .0001). At subsequent follow‐up visits, the VHI‐10 scores remained stable (mean, 8.3). This shift in VHI scores was accompanied by favorable improvements in both noise‐to‐harmonic ratio and speaking fundamental frequency in both males and females. Conclusions In‐office KTP ablation of vocal fold polyps had a favorable effect on patient‐reported handicap as determined by the VHI‐10. This treatment also slightly altered physiologic measures of voice; however, these measures did not achieve statistical significance. Level of Evidence 4. Laryngoscope, 124:1176–1179, 2014